RNF20 Is Critical for Snail-Mediated E-Cadherin Repression in Human Breast Cancer - Wang, Danping; Wang, Yifan; Wu, Xuebiao; Kong, Xiangxing; Li, Jun; Dong, Chenfang (Frontiers in Oncology, 2020)
E-cadherin, a hallmark of epithelial-mesenchymal transition (EMT), is often repressed due to Snail-mediated epigenetic modification; however, the exact mechanism remains unclear. In this study, we identified that Snail interacted with RNF20, an E3 ubiquitin-protein ligase responsible for monoubiquitination of H2BK120, and G9a, a methyltransferase for H3K9me2, and formed a Snail-RNF20-G9a complex. RNF20 expression led to the inhibition of E-cadherin expression in the human breast cancer cells. Mechanically, we showed that RNF20 and H3K9m2 were enriched on the promoter of E-cadherin and knockdown of Snail reduced the enrichment of RNF20, showing a Snail-dependent manner. RNF20 expression enhanced breast cancer cell migration, invasion, tumorsphere and colony formation. Collectively, RNF20 expression contributes to EMT induction through the epigenetic regulation of E-cadherin promoter, suggesting RNF20 as a potential target for treating breast cancer.